2004
DOI: 10.1158/0008-5472.can-03-3018
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Action of Secreted Phospholipase A2 in Prostate Cancer

Abstract: Mortality from prostate cancer is associated with progression of tumors to androgen-independent growth and metastasis. Eicosanoid products of both the cyclooxygenase (COX) and lipoxygenase (LOX) pathways are important mediators of the proliferation of prostate cancer cells in culture and regulate tumor vascularization and metastasis in animal models. Pharmacologic agents that block either COX or LOX products effectively reduce the size of prostate cancer xenografts. Phospholipase A 2 (PLA 2 ) enzymes regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 22 publications
5
96
0
6
Order By: Relevance
“…56,57 In line with the mitogenic function of PLA2 pathway products, inhibitors of PLA2s have been shown to block proliferation of human breast cancer-, promonocyticand prostate cancer cell lines. 33,58,59 Consistent with these reports, in vitro drug tests in our study showed that all three identified compounds inhibited proliferation and induced apoptosis in an APL cell line. Significantly, these findings highlight the potential of our drug screening strategy to identify candidate drugs with antileukemic effects that might be used as supplements in current APL treatment protocols.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…56,57 In line with the mitogenic function of PLA2 pathway products, inhibitors of PLA2s have been shown to block proliferation of human breast cancer-, promonocyticand prostate cancer cell lines. 33,58,59 Consistent with these reports, in vitro drug tests in our study showed that all three identified compounds inhibited proliferation and induced apoptosis in an APL cell line. Significantly, these findings highlight the potential of our drug screening strategy to identify candidate drugs with antileukemic effects that might be used as supplements in current APL treatment protocols.…”
Section: Discussionsupporting
confidence: 91%
“…The current standard regimes for APL therapy all include combinations of ATRA 33 and anthracycline-based chemotherapy. 5 Despite this, these regimens have markedly increased the rate of complete remission and the long-term outcome of APL patients, approximately 10-30% of patients will suffer from recurrent disease within a period of 5 years.…”
Section: Identification Of Candidate Drugs For the Treatment Of Aplmentioning
confidence: 99%
“…In particular, the overexpression of human sPLA 2 -IIA in gastric adenocarcinoma was proposed to be related to prolonged survival and less frequent metastasis (Leung et al, 2002;Aggarwal et al, 2006). By contrast, sPLA 2 -IIA overexpression has been associated to oncogenic effects in prostate cancer (Sved et al, 2004) and is related to poor prognosis (Graff et al, 2001). The polymorphism of the sPLA 2 -IIA gene, PLA2G2A, is also associated to some phenotypic features of patients with familial adenomatous polyposis (Yanaru-Fujisawa et al, 2007).…”
mentioning
confidence: 99%
“…However, despite the high number of membrane proteins they obtained, none of them are high molecular weight proteins. Interestingly, adenylate kinase and phospholipase A2 were shown to be over-expressed in prostatic cancer (43,44) and the putative SHBG receptor was also first described in the prostate (1). Given the association of these proteins with SHBG in the brain it is not known at this time if these proteins are also involved in brain cancer.…”
Section: Discussionmentioning
confidence: 99%